Factors related to the pre-eclampsia case in Oesapa Health Center, Indonesia - Acihayati, Justina Purwarini; Moeda, Serly Sandra (International Journal of Research in Medical Sciences, 2019)
Background: Pre-eclampsia is a special condition during pregnancy where hypertension and proteinuria occur after 20 weeks of gestation in mothers who have had normal blood pressure. The number of pregnant women with pre-eclampsia in the Oesapa Health Center since 2014-2015 has increased. The purpose of the study was to determine the factors associated with the incidence of pre-eclampsia in the Oesapa Health Center. Methods: This study was an analytic observational study with a case control research design through a retrospective approach. Bivariate data analysis with Chi Square Test and multivariate analysis with Logistic Regression. Results: Bivariate test results obtained data that there are 3 variables that have a relationship with the incidence of pre-eclampsia in pregnant women, namely age (p value 0.000, p <α), gravida status (p value 0.001) and Record of hypertension in the family (p value 0.000). Two variables did not have a relationship between the incidence of pre-eclampsia in pregnant women, namely education (p value 0.488, p> α) and respondent's work (p value 0.899). In the multivariate analysis, the factor that most influence the incidence of pre-eclampsia is age (p value 0.000). Conclusions: Health workers need to improve antenatal care, so that they can take maximum preventive action against all risky pregnant women.